Synthesis, crystal structure, and Helicobacter pylori urease inhibition of a dicyanoamide bridged Cu(I/II) complex. Issue 16 (17th August 2016) - Zhu, Yueyang; Wang, Cun-Fang; Yan, Kai; Zhao, Ke-Dong; Sheng, Gui-Hua; Hu, Qiqige; Zhang, Leiyu; You, Zhonglu
Abstract: A dicyanoamide-bridged polymeric copper(I/II) complex, [Cu II (sal)(bipy)Cu I (dca)2 ]n, was prepared by reaction of 5-methylchlorosalicylaldehyde (Hsal), 2, 2′-bipyridine (bipy), sodium dicyanoamide (Nadca), and copper perchlorate in methanol. The complex was characterized by elemental analyses, infrared and electronic spectroscopy, and single-crystal X-ray determination. Cu II has a square pyramidal coordination, and Cu I has triangular coordination. The complex showed high urease inhibitory activity with IC50 value of 0.16 ± 0.23 μM. Abstract :